A (in)visibilidade do Brasil rural no serviço social: o reconhecimento dos determinantes a partir da análise da mediação entre a formação e o exercício profissional em Alagoas - Lusa, Mailiz Garibotti (2012)
This study is about Social Work, the rural and the dialectic mediation between the formation and the professional exercise at the rural environment, at Alagoas State. The objective is to analyse how the first one produces theorical-methodologic help, technical-operative help and ethical-politic help, to the professional practice that occurs in rural social-occupational environments at that State. It s lead question is to understand the reason why, in having professional demands, the Social Work still made itself present but in a shy way at the rural reality. We work with two hypothesis which, although may look diametrically opposite, are mediated between themselves: the rural is marginal to the profession because the formation does not make possible elements for social assistants to look at and recognize it s demands, or it s the rural movement on the actual capitalism and the insipiense of the professional work that does not demand from the academy to discuss about this reality while a professional formation. Receives centrality the treatment of the brazilian social-historic formation, of the development of Social Work formation in Brazil, of the pedagogic route of the Social Work courses from UFAL and of mediations between the Professional work of social worker at rural social-occupational environments, at Alagoas, and the professional formation offered by UFAL. It s about the study based on the critical-dialectic method, with qualitative nature and study of exploratory type, even though in it s development it already advances to the level of description and explaining of the founded reality. It was used procedimental techniques of bibliological research, documentary research and empirical research, and this last one with the application of oriented interviews by a semistructured script, done with thirteen social worker who work at rural social-occupational environments at Alagoas and that were graduated in one of the two Social Work s courses of UFAL. It s concluded that some limits of professional formational pointed since the 70 s decade were not effectively overcome, existing two main obstacles for the Professional formation to prepare the social worker to work at rural environments: the historical emptiness when dealing with society and with the profession and fragmentation of reality. So, it s realized that the pretense perspective critical, historical, dialectic and totalizing of the analysis of social processes finds itself seriously threatened, having like main point of professional formation nowadays and the assurance of it s generalistic carachter and of the mediation between the three nucleus of fundaments of formation in Social Work